Users' intellectual property rights in crowdsourced software engineering tasks - Al-Bloush, Hani Barjes; Solemon, Badariah (2017)
Online crowdsourced software engineering (CSE) platforms users comprise of task requesters and workers (or participants).It is critical for the users to acquire the Intellectual Property Rights (IPRs) for CSE tasks in order to maintain and encourage software crowdsourcing practices. This paper aims to examine the different CSE tasks and IPRs to help researchers understand better how these IPRs can be effectively applied to CSE platforms.A mapping table between CSE tasks and their IPRs is offered in this paper as the results of a comprehensive review of IPRs (copyrights, patents, trade secrets, trademarks, industrial design and database rights) and CSE tasks (in different phases of software engineering) from a number of relevant researchers.The results of the study are expected to be beneficial to crowdsourcing participants in understanding their rights and to existing crowdsourcing platforms owners as well as companies that are planning to launch, particularly, new CSE platforms to leverage the crowd power of the software engineering society.